Research in Clinical Pragmatics - Cummings, Louise (Perspectives in Pragmatics, Philosophy & Psychology,, 2017)
This is the first volume to present individual chapters on the full range of developmental and acquired pragmatic disorders in children and adults. In chapters that are accessible to students and researchers as well as clinicians, this volume introduces the reader to the different types of pragmatic disorders found in clinical populations as diverse as autism spectrum disorder, traumatic brain injury and right hemisphere language disorder. The volume also moves beyond these well-established populations to include conditions such as congenital visual impairment and non-Alzheimer dementias, in which there are also pragmatic impairments. Through the use of conversational and linguistic data, the reader can see how pragmatic disorders impact on the communication skills of the clients who have them. The assessment and treatment of pragmatic disorders are examined, and chapters also address recent developments in the neuroanatomical and cognitive bases of these disorders.